Perencanaan Penjadwalan Preventive dan Proactive Maintenance Pada Dies Molding Capacitor - Benny Haddli Irawan; Hendri Tenis Agasi Siburian (Jurnal Teknologi dan Riset Terapan (JATRA), 2020)
Budget instability and increasing competition in the industrial world require companies to further improve the efficiency of their operations. A large level of downtime every month is very often found. Because the more downtime that occurs, the more detrimental to the productivity of a company. Disturbances that occur during the production process or routine activities that occur due to damage to machinery or other work facilities, must be prevented as early as possible. What is more important is that future disruptions do not occur again. Enhance the role of technicians and instructors as the maintenance team that first discusses the problem of engine failure that is used for practice to create integrated productive maintenance systems. Scheduled and planned maintenance can prevent damage to equipment and other work facilities. This research can eliminate simple examples of unnecessary damage. Approved preventive maintenance will produce an inventory of all components used that are delivered with scheduled maintenance. To carry out maintenance required work that is planned to be done in accordance with what will be done. The machine subject that is translated is the Printing Machine, where the machine's focus component to be allocated is a Dying Matter / Print Matter. From data processing and discussion, the most important parts are Cavity, Ejector Pin, Thermocouple, and Screw. The damage category found the recommended component replacement.